The chocolate moose motive [large type] : a chocoholic mystery - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2013)
As much as the chocolates at TenHuis tantalize people's tongues, Lee's newest hire makes them wag. Forsythia "Sissy" Smith is the granddaughter of Warner Pier's only remaining resident hippie. But now that's the least of Lee's concerns. The previous winter, Sissy's husband was shot to death, and in spite of her alibi local talk named Sissy the number one suspect. Then the chief gossip is found dead, with Sissy on the scene. Was she lured there? Or is she the killer?